Proposed South African management framework for the implementation of the International Convention for the Control and Management of Ships' Ballast Water and Sediments - Nolting, Janine (Rhodes University, Faculty of Commerce, Rhodes Business School, 2011)
South Africa, strategically situated at the southern tip of Africa, is edged on three sides by almost 3000 km of coastline surrounded by the Indian Ocean and the Atlantic Ocean (South African Tourism, 2011). This vast ocean expanse is responsible for conveying approximately 96% of South Africa's exports (Brand South Africa, 2011). Despite the positive economic effects of the shipping industry, translocation of harmful organisms and pathogens via ballast water and sediments inside ballast water tanks has far reaching global environmental (and economic) impacts (Oliviera, 2008:1; David and Gollasch, 2008:1966). Ballast water is the water that is taken on in order to manage the draft of the ship, to help with propulsion, manoeuvrability, trim control, list and stability (Oliviera, 2008:2). The discharge of ballast water into the world's oceans has resulted in the transfer of ecologically harmful sea-life into non-native environments (IMO, 2011), resulting in major environmental threats to our oceans (Bax, Williamson, Aguero, Gonzalez and Geeves, 2003:313). Various international documents have been developed to deal with the ballast water issue, culminating in the introduction of the International Convention for the Control and Management of Ships' Ballast Water and Sediments ("the Convention" ) in 2004. The Convention aims at achieving a reduction in the transfer and subsequent impacts of aquatic organisms via the ballast water and sediment of ships. On a local level, South Africa does not have direct legislation or regulations dealing with ballast water (Duncan, 2007:34) and relies on the combination of a number of pieces of legislation relating to environmental management, coastal management, biodiversity, alien invasive species control, port control and ship safety (National Environmental Management Act, 1998, National Environmental Management: Biodiversity Act, 2004, National Environmental Management: Integrated Coastal Management Act, 2009, National Ports Act, 2005 and Merchant Shipping Act, 1951). Although the Convention was ratified by South Africa in 2008 (Department of International Relations and Cooperation, 2011) it is still not in force and there still exists no other consolidated legal mechanism through which ballast water is managed. This research has investigated the various roles, responsibilities and mandates of South African competent authorities under the aforementioned legislation in managing ballast water, and has determined that there is definite legislative and institutional fragmentation as well as overlaps. A comparative analysis of management frameworks developed both locally and internationally was conducted in order to develop a management framework for ballast water management in South Africa. Various legislative, institutional and functional aspects were identified and adapted for inclusion in a South African management framework. A co-ordinated approach to ballast water management has been developed in the management framework which is anticipated to result in more definitive roles and responsibilities of the various South African departments involved in the management of ballast water and implementation of the Convention.
Keywords: Ships -- Fouling; Discharge of ballast water -- Environmental aspects; International Convention for the Control and Management of Ships' Ballast Water and Sediments; Nonindigenous aquatic pests -- Law and legislation; Marine fouling organisms -- Law and legislation